2009
DOI: 10.1364/oe.17.015700
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation suppression for stability improvement in Nd:YVO_4 regenerative amplifier

Abstract: Continuously pumped regenerative amplifiers are subject to energy instability at high pulse repetition rates due to period doubling bifurcation. Theoretical and experimental data are presented, in order to differentiate and understand instability effects in Nd:YVO4 regenerative amplifier, and possible techniques for performance optimization are analyzed. An increase in the seed pulse energy is demonstrated to improve amplification dynamics. Addition of a preamplifier is shown as an efficient way to achieve see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…Comprehensive utilization of these theoretical results has promoted top performance obtained from multi-kilohertz Yb:YAG disk amplifier (Metzger et al, 2009). Experimental study, performed with Nd:YVO 4 system, has thoroughly confirmed theoretical conclusions and on its basis the concept of regenerative amplifiers optimization has been formulated (Grishin et al, 2008;Grishin et al, 2009).…”
Section: Introductionmentioning
confidence: 70%
“…Comprehensive utilization of these theoretical results has promoted top performance obtained from multi-kilohertz Yb:YAG disk amplifier (Metzger et al, 2009). Experimental study, performed with Nd:YVO 4 system, has thoroughly confirmed theoretical conclusions and on its basis the concept of regenerative amplifiers optimization has been formulated (Grishin et al, 2008;Grishin et al, 2009).…”
Section: Introductionmentioning
confidence: 70%
“…1 at high RTs, was demonstrated in [3]. This was more precisely studied for an Nd:YVO 4 RA, showing bifurcation for a large range of RTs, prior to the start of further inherently stable RTs [5]. More recently, this was demonstrated, for the first time, for an Ho:YLF RA [6], achieving high pulse energies by overcoming bifurcation instability at a repetition rate of 1 kHz.…”
mentioning
confidence: 88%
“…The regimes were generally observed in experiments, for example, in [5,19], but there has not been a study of these regimes as a function of the pump intensity, repetition rate, and seed fluence. Figure 3a illustrates the four characteristic operation regimes (①-④) for regenerative amplification as a function of the repetition rate and pump intensity.…”
Section: Operation Regimes Of Regenerative Amplifiersmentioning
confidence: 99%
“…Unlike the regenerative amplifier scheme which is hard to stay stable at high repetition rate [14] , 2 W. Chen et al Figure 1. Setup of the all PM fiber mode-locked laser.…”
Section: Introductionmentioning
confidence: 99%